Do campo para a cidade: estudo sobre feiras livres, abastecimento urbano e comercialização da agricultura familiar no Alto Jequitinhonha - Maria Sirlene da Cruz (2019)
This paper addresses the relationship between local food production and consumption, highlighting free fairs and urban trade as short marketing circuits and spaces of sociability between farmers and consumers in five municipalities of the Territory of Alto Jequitinhonha, Minas Gerais. Here are presented three studies that had as main objectives to analyze the dynamics of the commercialization of family agriculture in the free fairs; analyzing the importance of these free trade fairs for urban supply and food security and sovereignty; and analyzing the entry of rural domestic industry products into urban trade. To achieve these objectives, methodologies that allow qualitative and quantitative analysis were used. Primary information was collected through interviews with 94 traders, 230 consumers and 24 traders in the cities surveyed. Secondary sources (literatures and databases on the subject) were also consulted. The results indicate that free fairs generate income for farmers, supply a significant portion of the urban population, promote food security and sovereignty and represent the main direct selling channel for family farming in the territory under study. However, it is essential to think about actions and policies aimed at strengthening and rural development to overcome difficulties of access to markets and create strategies that promote the appreciation of the attributes that are rooted in culture and in the way of life of society, adding value to products in the territory.